Five‐year clinical results for treatment of intrabony defects with EMD, guided tissue regeneration and open‐flap debridement: a case series. (12th May 2014) - Mitani, A.; Takasu, H.; Horibe, T.; Furuta, H.; Nagasaka, T.; Aino, M.; Fukuda, M.; Fujimura, T.; Mogi, M.; Noguchi, T.
<x xml:space="preserve">Abstract</x> Background and Objective Although regenerative periodontal surgery with EMD or guided tissue regeneration (GTR) has been shown to enhance periodontal regeneration, there are limited data on the long‐term results following these treatment modalities. The purpose of the present study was to investigate the long‐term clinical outcomes in intrabony defects following regenerative periodontal surgery with EMD or GTR compared with open‐flap debridement (OFD). Material and Methods Data from 40 subjects (44 teeth), with no history of smoking or systemic diseases that could interfere with periodontal disease and who received one of three surgical procedures (EMD, GTR or OFD) for two‐ or three‐wall intrabony defects, were analyzed. Postoperative reduction in probing pocket depth, gain in clinical attachment level, gingival recession and percentage bone fill were compared at 1, 3 and 5 years. Results Reduction in probing pocket depth after GTR was significantly higher than after OFD at 1 and 3 years postoperatively, but there was no difference between the groups at 5 years. The gains in clinical attachment level for EMD (at 3 and 5 years) and for GTR (at 1, 3 and 5 years) were significantly greater than for OFD. Gingival recession after treatment with EMD and GTR showed a tendency toward positive results, whereas no such tendency was observed for OFD. Postoperative percentage bone fill for EMD and GTR was significantly greater than for OFD at 3 and 5 years. Conclusions This is a retrospective study and an exploratory report with a high risk of bias. Within the limits of the current study, it may be concluded that superior gains in clinical attachment level and improved percentage bone fill can be obtained with EMD and GTR when compared with OFD, and these can be maintained over a period of 5 years.